221k views
5 votes
Given: 3x = 5 (x − 4) Prove: x = 10

========================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================











Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10

Given: 3x = 5 (x − 4) Prove: x = 10 ======================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================== Given-example-1
User Jayphelps
by
5.1k points

1 Answer

4 votes

Answer:

see the procedure

Explanation:

we have


3x=5(x-4)

step 1


3x=5(x-4) ------> given problem

step 2

Applying the Distributive Property right side


3x=5(x)-5(4)


3x=5x-20

step 3

Applying the Subtraction Property of Equality

Subtract (3x-20) both sides


3x-(3x-20)=5x-20-(3x-20)


20=2x

step 4

Applying Division Property of Equality

Divide by 2 both sides


20\2=x

Rewrite


x=10

User Tim Bassett
by
5.8k points